2008
DOI: 10.1098/rstb.2008.0192
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of recovery following early visual deprivation

Abstract: Natural patterned early visual input is essential for the normal development of the central visual pathways and the visual capacities they sustain. Without visual input, the functional development of the visual system stalls not far from the state at birth, and if input is distorted or biased the visual system develops in an abnormal fashion resulting in specific visual deficits. Monocular deprivation, an extreme form of biased exposure, results in large anatomical and physiological changes in terms of territo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 110 publications
1
46
0
1
Order By: Relevance
“…The range and average age of the mice for each subgroup were as follows: WT no MD: age range: 1.9 -3.5 months, average 2.8 months, WT MD: age range 1.7-10.5 months, average 4.8 months, Lynx1 KO no MD: 4 -7.5 months, average 6.4 months, Lynx1 KO MD: 2.8 -7.4 months, average: 5.3 months, DKO no MD: 2.5-4.2 months, average: 3.2 months, and DKO MD: 2.5-4 months, average 3.6 months. All mice but one WT no MD mouse and two WT MD mice were older than P72, when no OD plasticity is detected after 4 d of MD (Stodieck et al, 2014). Among WT mice with MD, there was no statistically significant difference in OD plasticity (CBI) between adult mice group younger than P72 (2 mice) versus mice group older than P72 (5 mice) ( p ϭ 0.599, t test), or between adult mice younger than P110 (3 mice) versus fully adult mice older than P110 (4 mice) subgroups ( p ϭ 0.253, t test).…”
Section: Tpa Is Required For the Elevated Od Plasticity In Adult Lynxmentioning
confidence: 99%
See 2 more Smart Citations
“…The range and average age of the mice for each subgroup were as follows: WT no MD: age range: 1.9 -3.5 months, average 2.8 months, WT MD: age range 1.7-10.5 months, average 4.8 months, Lynx1 KO no MD: 4 -7.5 months, average 6.4 months, Lynx1 KO MD: 2.8 -7.4 months, average: 5.3 months, DKO no MD: 2.5-4.2 months, average: 3.2 months, and DKO MD: 2.5-4 months, average 3.6 months. All mice but one WT no MD mouse and two WT MD mice were older than P72, when no OD plasticity is detected after 4 d of MD (Stodieck et al, 2014). Among WT mice with MD, there was no statistically significant difference in OD plasticity (CBI) between adult mice group younger than P72 (2 mice) versus mice group older than P72 (5 mice) ( p ϭ 0.599, t test), or between adult mice younger than P110 (3 mice) versus fully adult mice older than P110 (4 mice) subgroups ( p ϭ 0.253, t test).…”
Section: Tpa Is Required For the Elevated Od Plasticity In Adult Lynxmentioning
confidence: 99%
“…The range and the average age of mice for each subgroup were as follows: WT no MD: 2.6 -6.8 months, average 6.1 months, WT MD: 2.6 -6.8 months, average 4.7 months, Lynx1 KO no MD: 2.4 -13.1 months, average 8.1 months, and Lynx1 KO MD: 2.3-11.0 months, average 5.9 months. As a recent study reported, no significant OD plasticity in WT mice ϳP72 (age range P57-P80) (Stodieck et al, 2014), we also compared the tPA activity only with the mice older than P72 (excluding 2 mice each from KO noMD group and KO MD group who were younger than P72). In these sets of mice over P72, Lynx1KO MD groups (14 mice) maintained a statistically significant increase in tPA activity compared with age-matched controls ( p ϭ 0.031 vs WT MD group, 12 mice; p ϭ 0.020 vs Lynx1 KO no MD group, 16 mice, t test).…”
Section: Tpa Activity Elevates In Adult V1 Following MD In Lynx1 Ko Micementioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments have shown that the reduction of responses from the deprived eye occurs rapidly, followed by a slower increase of drive from the nondeprived eye (6,7). Recovery of deprived eye responses after eye reopening occurs robustly (8,9), although its time course has not been well studied.…”
mentioning
confidence: 99%
“…It therefore follows that deprivation or overloading of a certain sensory experience may affect the function of those receiving brain regions [9]. It is well-known that visual deprivation promotes the somatosensory or auditory system in animal models as well as in humans [10]. Especially, the abnormal sensory stimulation in the early life (e. g. juvenile and adolescent periods) can disturb the normal structure and function of brain circuits [11,12].…”
Section: Introductionmentioning
confidence: 99%